The Politics of the Womb': Women, Politics and The Environment in Pre-Colonial Chivi, Southern Zimbabwe, c.1840 to 1900* - Mazarire, Gerald C. (University of Zimbabwe Publications, 2016)
http://pdfproc.lib.msu.edu/?file=/DMC/African%20Journals/pdfs/Journal%20of%20the%20University%20of%20Zimbabwe/vol30n1/juz030001004.pdf